ABOUT THE USE OF UNIVERSAL MAGNETIC CHARACTERISTICS TO CALCULATE THE ELECTROMECHANICAL CHARACTERISTICS OF TRACTION MOTORS - Getman, H. K.; Golik, S. M. (Science and Transport Progress, 2007)
The idea of increase the calculations exactness based on application of universal magnetic characteristic due to value variation of satiation factor is considered.